CURRENT ROLE OF SOCIAL MEDIA IN AESTHETIC PLASTIC SURGERY: WHY PLASTIC SURGEONS MUST TAKE CONCERN? - Amandita, Tiara Amanna; Saraswati, Hastika (Jurnal Rekonstruksi dan Estetik, 2023)
Highlights: This study shows that in the era of society 5.0, digital technology has played a major role in doctor-patient communication in the medical field, especially in plastic aesthetic surgery. Only a few plastic surgeons comprehend this digital transformation. It is hoped that this study will help plastic surgeons better understand and adapt to social media. Abstract: Introduction: In the medical field, particularly in areas like plastic aesthetic surgery and cosmetology, social media has emerged as a convenient and interactive means of educating and promoting the services of doctors, hospitals, and institutions. However, there remains a pressing need for further research to thoroughly understand the influence of social media on plastic surgery procedures. This study aims to review the literature on the current facets of social media that impact patients' decision-makingin aesthetic plastic surgery. Methods: Database PubMed was used for the search terms: "plastic surgery," aesthetic, and "social media". Publication time ranges were set from 2019 until 2023. Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) were used to help arrange this literature review. Result: Thirteen records were included in this study. The studies uniformly emphasize the effectiveness of social media as a communication tool between doctors and patients or social media users. Popular platforms like Facebook, Instagram, Snapchat, and Twitter are widely used, varying based on factors like country, age, and gender. These platforms enable the global spread of education and information about plastic aesthetic surgery, effectively reaching a diverse audience. Conclusion: Social media serves as a platform for disseminating educational content, promoting professional work, engaging with the wider public community, and facilitating patient-doctor interactions in the decision-making process for plastic aesthetic surgery. Additionally, it plays a role in influencing patients' preferences regarding specific aesthetic plastic surgery procedures.